Theorie der Klassik Eine kulturelle Praxis von Goethe bis Grandmaster Flash - Wojcik, Paula (De Gruyter, 2022)
For the last three centuries, prominent thinkers have been asking themselves what it is that constitutes a classic. This volume takes up this question and shows how cultural artifacts become and remain classics through transcultural circulation, i.e., through their adaptation in ever-changing media and the expansion of the cultural milieu in which they are received.